The Mechanism of Induced Seismicity 2002
DOI: 10.1007/978-3-0348-8179-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Induced Microearthquake Patterns in Hydrocarbon and Geothermal Reservoirs: Six Case Studies

Abstract: The injection or production of fluids can induce microseismic events in hydrocarbon and geothermal reservoirs. By deploying sensors downhole, data sets have been collected that consist of a few hundred to well over 10,000 induced events. We find that most induced events cluster into well-defined geometrical patterns. In many cases, we must apply highprecision, relative location techniques to observe these patterns. At three sedimentary sites, thin horizontal strands of activity are commonly found within the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 32 publications
3
51
0
Order By: Relevance
“…In contrast, studies of hydrofracture-induced microearthquakes, especially in tight-gas environments, typically find b values of 2.0 and higher; indeed, Dinske (2009a, 2009b) report b of 2.50 for microearthquakes produced by hydrofracturing the Barnett shale. Second, the cumulative number and cumulative moment of microearthquakes induced by hydrofracture tends to increase linearly with the volume of fluid injected (e.g., Phillips et al, 2002;Rutledge et al, 2004;Shapiro and Dinske, 2009b), rather than occurring in bursts or clusters as is observed for DFW in Figures 4 and 13. Finally, the largest DFW earthquakes have similar magnitudes (M 3.3) to historical natural earthquakes in northeast Texas.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, studies of hydrofracture-induced microearthquakes, especially in tight-gas environments, typically find b values of 2.0 and higher; indeed, Dinske (2009a, 2009b) report b of 2.50 for microearthquakes produced by hydrofracturing the Barnett shale. Second, the cumulative number and cumulative moment of microearthquakes induced by hydrofracture tends to increase linearly with the volume of fluid injected (e.g., Phillips et al, 2002;Rutledge et al, 2004;Shapiro and Dinske, 2009b), rather than occurring in bursts or clusters as is observed for DFW in Figures 4 and 13. Finally, the largest DFW earthquakes have similar magnitudes (M 3.3) to historical natural earthquakes in northeast Texas.…”
Section: Discussionmentioning
confidence: 83%
“…In this paper we investigate which activities related to natural gas recovery might possibly have induced the earthquakes, that is, drilling, hydrofracture, production, or fluid waste disposal. We will also compare the properties of the DFW sequence to natural and human-induced earthquake sequences in Texas and elsewhere (e.g., see Phillips et al, 2002;Majer et al, 2007;Suckale, 2009Suckale, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…They also identify a trailing aseismic zone, which they suggest may be related to the fracture length that is maintained open and thus available for propant placement. The aseismic zone attained lengths of about one-third to one-half of total seismic length, suggesting potentially conductive hydrofrac lengths of 61 to 198 m. Long seismic lengths (over 760 m) were also identified for an injection in the Austin Chalk (Phillips et al, 2002), though again, a lack of conductivity was observed based on production performance. Work in other environments has found much shorter lengths.…”
Section: Hydraulic Fracture Lengthmentioning
confidence: 93%
“…In practice, this appears to often work well in sedimentary environments. Phillips et al (2002) observed a strong tendency for microseismicity induced by fluid injection to organize into thin, roughly horizontal strands of activity in clastic sedimentary environments. The near-horizontal orientations led them to suspect that stratigraphy controls fracture behavior, with stratigraphic changes limiting fracture growth through an increase in ductility or an increase or decrease in mechanical strength and supported stress at a layer boundary.…”
Section: Vertical Extent Of Hydraulic Fracturesmentioning
confidence: 96%
See 1 more Smart Citation